A novel fasting regimen revealed protein reservation and complement C3 down-regulation after 14-day’s continual dietary deprivation - Hao, Yaqian; Fu, Yu; Sun, Liangliang; Yu, Yaying; Min, Xia; Wei, Qiannan; Huang, Shuangjian; Zhao, Sen; Wang, Li; Wang, YuanYuan; Li, Yangyang; Zheng, Xia; et al. (Frontiers in Endocrinology, 2023)
Objectives: The aim is to evaluate the effect of a novel 14-day fasting regimen on the balance between skeletal muscle and adipose tissue composition which might associate with inflammatory factors. Our analysis includes basic physical examinations, clinical laboratory analysis, bioelectrical impedance and biochemical analytic assessments of healthy volunteers. Methods: Eight healthy subjects were randomly selected from a pool of volunteers to undergo a continual dietary deprivation (CDD) regimen. Individuals were assigned to take Flexible Abrosia (FA, prebiotic combination) plus appropriate mineral supplement of potassium and magnesium at 3 mealtime every day to prevent potential injury from starved intestinal flora and avoid spasms of smooth muscle due to hunger. Physical and medical examinations were conducted and blood samples were collected at following timepoints: before CDD as self-control (0D), day 7 and day 14 during fasting, and 7-21days and/or 2~3mo after refeeding. Results: The combination of FA and mineral supplements significantly decreased self-reported physical response of starvation, with tolerable hunger-mediated sensations experienced during CDD. Bioelectrical and biochemical results indicated significant reduction in both muscle lean and fat mass on day 7. Meanwhile, markers related to fat composition consistently decreased during and after CDD. In addition, most biochemical marker levels, including serum proteins, reached their inflection points at the 7th day of CDD as compared to the control measurements. Levels of these factors started to show a relative plateau, or reversed direction upon the 14th day of CDD. The exceptions of above factors were myostatin and complement protein C3, which remained at lower concentrations in the blood throughout CDD, and were unable to fully recover toward baseline levels even after 3 months’ refeeding. Conclusion: Our results indicated that human subjects undergoing prolonged dietary restriction were well protected by FA and mineral ions from gut injury or physical discomfort of starvation. Most factors showed a relative plateau response at the end of 14D-CDD. The muscle tissues were well preserved during prolonged fasting, and an improved protein/lipid ratio was observed. Upon refeeding, constant lower levels of myostatin and complement C3 were maintained after CDD implies a long-term beneficial effect in dealing with anti-aging and inflammation.